Involving citizens: Highlights from more than 10 years of Ukrainian-Norwegian research collaboration on local community development and local democracy - Aadne Aasland (Харків: ХНУ імені В.Н. Каразіна, 2019)
The local level is an important arena for the practice of democracy. It is at the local level that people encounter concrete social problems, and it is above all there that they expect the delivery of effective policies and solutions. Therefore, the local level has been seen as the key location for the appearance and application of democratic initiatives that can eventually lead to transformation of the social and economic sectors in a state as a whole. In Ukraine, despite the existence of various instruments of citizens’ interaction with the authorities, a large segment of the population has for various reasons remained detached from the processes of development, adoption, and implementation of governmental decisions. Moreover, many local governmental institutions have failed to use the existing potential for involving the citizenry in solving local problems.
Aadne Aasland, Senior researcher, Norwegian Institute for Urban and Regional Research (NIBR), OsloMet – Oslo Metropolitan University.
Keywords: Research Subject Categories::SOCIAL SCIENCES; норвезько-українська конференція